Hubungan Empati dengan Caregiver Burden pada Family Caregiver Orang dengan Skizofrenia (ODS) (Jurnal Ilmiah Psikologi MIND SET, 2025)
This study aims to examine the relationship between empathy and caregiver burden among family caregivers of People with Schizophrenia (PWS) in the Komunitas Peduli Skizofrenia Indonesia (KPSI). The participants in this study were family members who had been directly caring for individuals with schizophrenia for at least one year, were between 31 and 60 years old, and were members of the community. A total of 103 participants were recruited using purposive sampling. The instruments used in this study were the Basic Empathy Scale – Adult (2013) to measure empathy, and the Zarit Burden Interview – Short Version (2001) to assess caregiver burden. Data were analyzed using Spearman’s correlation analysis. The results indicated a significant positive relationship between both affective empathy and cognitive empathy with caregiver burden among family caregivers of individuals with schizophrenia. This suggests that higher levels of affective and cognitive empathy are associated with greater perceived caregiver burden. These findings highlight that empathy does not always have a positive impact on caregivers.